(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the portrayal of American society in the 20th century through the literary works of Theodore Dreiser and Joyce Carol Oates. Both authors provide profound insights into the complexities of social, economic, and cultural dynamics during this transformative period. Dreiser’s naturalistic approach reveals the struggles of individuals facing the harsh realities of urban life and the elusive American Dream, as seen in novels like Sister Carrie and An American Tragedy. In contrast, Oates’s diverse narratives, such as We Were the Mulvaneys and Blonde, explore themes of identity, gender, and societal expectations, often highlighting the psychological impact of societal pressures on her characters. By comparing their depictions, this article illustrates how both authors capture the intricacies of American life, reflecting broader themes of ambition, disillusionment, and resilience. Ultimately, their works serve as critical commentaries on the American experience, offering valuable perspectives on the enduring struggles and aspirations of individuals within a changing society.